Biorefinery 2030 : future prospects for the bioeconomy /: future prospects for the bioeconomy. (2015) - Schieb, Pierre-Alain; Lescieux-Katir, Honorine; Thénot, Maryline; Clément-Larosière, Barbara
No abstract available